(untitled) (Latin American Journal of Sedimentology and Basin Analysis, 2024)
The current study is centered on the morphological, textural, and compositional characterization of several linear landforms identified in the west and center of the Fiambalá Valley, in the western region of the Catamarca province (Argentina), along the terraces of the Apocango River. These landforms are slightly asymmetric to symmetric, with rounded crests, a few meters high (between 0.3 and 3.5 m) and several meters wide (from 8 to 14.5 m). They have straight to slightly sinuous ridges with NE-E to SW-W direction and are arranged as isolated bodies. The superficial cover has a bimodal frequency distribution with a primary mode in medium to coarse pebble (-4.5 to -3.5 ?) and a secondary mode in fine sand (2.5 ?). Gravel clasts are sub-rounded, with moderate sphericity, and predominantly compact-elongated shape. The analysis of high-resolution photographs of the superficial cover showed they present an open to moderate packing (44.49 - 58.60% of clasts). In a cross-sectional profile, it was observed that internally they consist of fine to medium sand (x: 2.66 - 1.31 ?). Gravel composition is made primarily by clasts of green sedimentary lithics (22.92 - 32.72%), followed by acidic volcanic lithics (15 - 21.49%), purple sedimentary lithics (13.72 - 17.04%), and basic (10.60 - 17.78%) and intermediate (9.74 - 12.93%) volcanic lithics, thus classified as lithic gravels. The sandy fraction is composed of lithics (35.71 - 47.51%), followed by quartz (23.59 - 37.92%), and feldspars (19.80 - 32.76%); consequently, classified as feldspathic litharenites. Regarding the lithic fragments, volcanic types predominate (27.41 - 37.70%), being those of acidic composition with felsitic and microgranular paste (20.06 - 31.15%) the most represented. The thicker superficial cover with open to moderate packing is interpreted as poorly evolved desert pavement. Deposit composition suggests that the main contribution of the gravelly and sandy material comes from the west (Sistema de Famatina), congruent with the source area of the Apocango alluvial system and the preferential directions of wind that transports material from the SW-WSW towards NNE-NE. The rounded crest, straight to slightly sinuous ridges, and their parallel orientation to the main drift potential direction (RDD) agree with the characteristics of moderately to highly deflated linear dunes. Regarding their origin, initially, the area was dominated by eolian sedimentation of linear dunes associated with the migration of wind ripples. In a second stage deflation prevailed, preserving only fine sediments in sheltered areas, probably related to the margins of small secondary channels or gullies. In this stage, active deflation altered the original linear dune morphology and gave rise to poorly evolved desert pavements. This process stabilized linear dunes, forming a protective layer and ensuring immobility.